Chronic toxicity of triazine-based and non-triazine ultraviolet filters toward Chlorella vulgaris: Low ecological risk of triazine-based compounds - Yuhao Yan; Hong Gao; Rundong Chen; Zhigang Wang; Cheng Zeng; Jia Yuan; Jianjun Liu; Rong Chen (Bioresource Technology, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

Electrostatically assembled gold nanocluster-enhanced porphyrinic metal-organic framework nanozymes for oxygen-boosted photodynamic therapy of hypoxic tumors - Ao He; Juan Zhou; Jing Zhu; Guojing Hong; Minglan Fan; Yuyan Bao; Rong Li; Manxiao Cheng; Xiang Ran (Journal of Photochemistry and Photobiology B: Biology, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

A Survey of the Species Origins of Common Fish Cell Lines—With a Particular Focus on the Grass Carp Ovarian Cell Line ( GCO ) - Hong Yang; Mijuan Shi; Yingyin Cheng; Wanting Zhang; Bin Gui; Rong Huang; Yaping Wang; Xiao‐Qin Xia (Journal of Fish Diseases, 2026)
Cell line misidentification or contamination undermines the reliability of research outcomes. In this study, we verified the species origin of commonly used fish cell lines, with a particular focus on the grass carp ovarian cell line (GCO). RNA‐seq data from 146 samples of 11 widely used fish cell lines were collected from public databases (NCBI‐SRA) and were mapped to the reference genomes of eight species. GCO RNA‐seq samples from three Chinese laboratories showed a mapping rate of 21.64% ± 3.61% to the grass carp genome, but 89.81% ± 4.83% to the fathead minnow genome. Further transcriptomic similarity analysis revealed that these GCO RNA‐seq samples clustered more closely with cell lines originating from fathead minnow. Targeted analysis of the COI gene amplification region confirmed that nearly all reads from GCO RNA‐seq samples mapped exclusively to the fathead minnow COI amplicon. Collectively, these results indicate that GCO may have undergone cross‐contamination or species misidentification. This study raises doubts about the true species origin of the GCO cell line and proposes that COI DNA barcoding can be used to discriminate the species origin of fish cell lines.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Polyprenylated acylphloroglucinols from Hypericum monogynum and their reversal of multidrug resistance in MCF-7/ADR cells - Yan-Rong Zeng; Peng Zhao; Jing-Yi Yin; Hong-Jin Ban; Zhan Feng; Yu-Xiang Li; Min Yang; Jing Tan; Cheng-Jian Tan; Jue Yang; Xiao-Jiang Hao; Chun-Mao Yuan (Molecular Diversity, 2026)

Seneca Valley virus 2B and 3 C proteins attenuate the cGAS-STING signaling pathway by targeting STING for degradation - Xuexia Wen; Meijun Zhou; Shijie Xie; Jin Yuan; Yu Hong; Ruiyi Ma; Liwei Zhao; Dan Wang; Rong Quan; Peipei Cheng; Jiangwei Song (Veterinary Microbiology, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Mechanisms of failure and permeability evolution in gas-bearing strata under tunnel-induced stress paths - Jiafeng Tan; Deyi Jiang; Rong Liu; Yi He; Jinyang Fan; Jianyu Liang; Cheng Qian; Hanlin He; Hong Zheng (Transportation Geotechnics, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Mechanoluminescent Janus architecture for stimulus-responsive photodynamic therapy - Rong-Kai Du; Xu-Lin He; Qing-Qing Jin; Hong Liang; Tai-Zhong Xiao; Lei Zhong; Jun-Cheng Zhang; Tian-Ying Sun; Lei Zhou; Ming-Mei Wu (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

One new aryltetralin lignan and other components from Blachia pentzii - Yan-Yan Zhang; Feng-Cheng Zhang; Yue Zhang; Hong-Yan Yu; Hai-Rong Xu; Xiao-Yun Dong; Chang-Shui Yang (Phytochemistry Letters, 2025)

Physicochemical properties and molecular adaptations of Bacillus velezensis Huang in response to ethanol stress - Guidong Huang; Qiushi Cheng; Jianwei Zheng; Hong Ren; Rong Huang; Manshi Ye; Jiayi Liu; Kaijie Zhong; Xianfeng Zhong (Food Research International, 2025)

Short-term ozone exposure and schizophrenia hospitalization risk: temperature modifying effect and greenspace mitigating effect - Chuan Li; Xin Yu; Rong Song; Yanhong Fang; Jiayuan Yang; Zhiyuan Tang; Shaoqi Wang; Xunrong Cheng; Weizhuo Yi; Rubing Pan; Jian Song; Hong Su (Environmental Pollution, 2025)

Characterization of neutral fluids in the volcanic geothermal system under the Tatun Volcano Group, Taiwan - Yi-Chia Lu; Chyi Wang; Sheng-Rong Song; Pei-Ling Wang; Ting-Jui Song; Sachihiro Taguchi; Tsung-Ren Peng; Li-Hung Lin; Jian-Cheng Lee; Hong-Chun Li (Journal of Geochemical Exploration, 2025)

Discovery and profiling of efficient microbial strains for struvite biomineralization in high-salinity wastewater - Bing-bing Liu; Rong-ji Zhao; Nimaichand Salam; Shu-hong Xu; Rong Shi; Jiang-hao Zhu; Zi-qing Chen; Cheng-yin Liu; Bing Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Postnatal exposure to various benzophenones at environmentally relevant levels enhances the susceptibility of mammalian testes to cyclophosphamide-induced spermatogenic stress in adulthood - Yan-Rong Gao; Ya-Jia Pu; Yu-Xin Sheng; Bin Cheng; Li-Jie Wang; Ya-Nan Tian; Jing Pu; Hui-Ming Ma; Hong-Mei Li; Hai-Ming Xu (Environmental Pollution, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Effect of culturing factors on the production of biomass and secondary metabolites in ginseng adventitious root cultures for new resource food - Hang-Lin Song; Zheng-Hai Cheng; Rong-De Jin; Chun-Guang Liu; Xiang-Hong Ma; Jun-Nan Wu; Xi-Hua Cui (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Intercomparison of radar data assimilation systems for snowfall cases during the ICE-POP 2018 - Ji-Won Lee; Ki-Hong Min; Kao-Shen Chung; Cheng-Rong You; Chieh-Ying Ke; GyuWon Lee (Atmospheric Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Blood cadmium levels and overactive bladder in middle-aged and older adults in the United States: Insights from NHANES 2007–2020 data - Fan Gao; Yin Lu; Qiang Cheng; Qing Ai; Bin Jiang; Zhen-Jun Luo; Guo-Rong Yang; Kai-Kai Lv; Qing Yuan; Hong-Zhao Li (Environmental Pollution, 2024)

FGTN: Fragment-based graph transformer network for predicting reproductive toxicity - Jia-Nan Ren; Qiang Chen; Hong-Yu-Xiang Ye; Cheng Cao; Ya-Min Guo; Jin-Rong Yang; Hao Wang; Muhammad Zafar Irshad Khan; Jian-Zhong Chen (Archives of Toxicology, 2024)

Azotosporobacter soli gen. nov., sp. nov., a novel nitrogen-fixing bacterium isolated from paddy soil - Cheng-Jie Xie; Ling Yao; Rong Tang; Shuang Han; Shang Yang; Hend Alwathnani; Christopher Rensing; Guo-Hong Liu; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2024)

Two novel Fe(III)-reducing bacteria, Geothrix campi sp. nov. and Geothrix mesophila sp. nov., isolated from paddy soils - Shuang Han; Shang Yang; Rong Tang; Cheng-Jie Xie; Xing Liu; Guo-Hong Liu; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Impaired thyroid hormone sensitivity exacerbates the effect of PM2.5 and its components on dyslipidemia in schizophrenia - Jintao Liu; Yinguang Fan; Jian Song; Rong Song; Xuanxuan Li; Li Liu; Ning Wei; Jiajun Yuan; Weizhuo Yi; Rubing Pan; Xiaoyu Jin; Jian Cheng; et al. (Science of The Total Environment, 2024)

The cytochrome P450 gene CYP4g1 driven by high temperature confers abamectin tolerance on Liriomyza trifolii through promoting cuticular hydrocarbons biosynthesis - Yu-Cheng Wang; Ya-Wen Chang; Hong-Fang Xie; Wei-Rong Gong; Cheng-Dong Wu; Yu-Zhou Du (Pesticide Biochemistry and Physiology, 2024)

Incorporation of atomic Fe-oxide triggers a quantum leap in the CO2 methanation performance of Ni-hydroxide - Amisha Beniwal; Dinesh Bhalothia; Yin-Rong Chen; Jui-Cheng Kao; Che Yan; Nozomu Hiraoka; Hirofumi Ishii; Mingxing Cheng; Yu-Chieh Lo; Xin Tu; Yun-Wei Chiang; Chun-Hong Kuo; et al. (Chemical Engineering Journal, 2024)

Collective effects of rising average temperatures and heat events on oviparous embryos - Liang Ma; Dan‐Yang Wu; Yang Wang; Joshua M. Hall; Chun‐Rong Mi; Hong‐Xin Xie; Wei‐Jie Tao; Chao Hou; Kun‐Ming Cheng; Yong‐Pu Zhang; Ji‐Chao Wang; Hong‐Liang Lu; et al. (Conservation Biology, 2024)
Survival of the immobile embryo in response to rising temperature is important to determine a species’ vulnerability to climate change. However, the collective effects of 2 key thermal characteristics associated with climate change (i.e., rising average temperature and acute heat events) on embryonic survival remain largely unexplored. We used empirical measurements and niche modeling to investigate how chronic and acute heat stress independently and collectively influence the embryonic survival of lizards across latitudes. We collected and bred lizards from 5 latitudes and incubated their eggs across a range of temperatures to quantify population‐specific responses to chronic and acute heat stress. Using an embryonic development model parameterized with measured embryonic heat tolerances, we further identified a collective impact of embryonic chronic and acute heat tolerances on embryonic survival. We also incorporated embryonic chronic and acute heat tolerance in hybrid species distribution models to determine species’ range shifts under climate change. Embryos’ tolerance of chronic heat (T‐chronic) remained consistent across latitudes, whereas their tolerance of acute heat (T‐acute) was higher at high latitudes than at low latitudes. Tolerance of acute heat exerted a more pronounced influence than tolerance of chronic heat. In species distribution models, climate change led to the most significant habitat loss for each population and species in its low‐latitude distribution. Consequently, habitat for populations across all latitudes will shift toward high latitudes. Our study also highlights the importance of considering embryonic survival under chronic and acute heat stresses to predict species’ vulnerability to climate change.

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

Capnesterones A and B, new steroids isolated from the soft coral Capnella imbricata - Ting-Yu Cheng; Chia-Jung Yang; Po-Jen Chen; Yu-Li Chen; Bo-Rong Peng; Te-An Kung; Zhi-Hong Wen; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Efficient magnetic enrichment cascade single-step RPA-CRISPR/Cas12a assay for rapid and ultrasensitive detection of Staphylococcus aureus in food samples - Yujie Ma; Hongjuan Wei; Yunxiang Wang; Xiaodan Cheng; Hong Chen; Xingsheng Yang; Hongsheng Zhang; Zhen Rong; Shengqi Wang (Journal of Hazardous Materials, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

Litter traps: A comparison of four marine habitats as sinks for anthropogenic marine macro-litter in Singapore - Jenny Fong; Samuel Hsien Rong Lee; Yuchen Sun; Cheng Ling Lim; Yean Ai Jolin Tan; Yi Hong Tan; Mei Lin Neo (Marine Pollution Bulletin, 2023)

Association between vitamin D supplementation and cancer incidence and mortality: A trial sequential meta-analysis of randomized controlled trials - Zhangyou Guo; Ming Huang; Dandan Fan; Yuan Hong; Min Zhao; Rong Ding; Yao Cheng; Shigang Duan (Critical Reviews in Food Science and Nutrition, 2023)

Superior performance of a membrane bioreactor through innovative in-situ aeration and structural optimization using computational fluid dynamics - Liguo Shen; Qihang Wu; Qunfeng Ye; Hongjun Lin; Jianzhen Zhang; Cheng Chen; Rong Yue; Jiaheng Teng; Huachang Hong; Bao-Qiang Liao (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The global burden of schizophrenia and the impact of urbanization during 1990–2019: An analysis of the global burden of disease study 2019 - Xuanxuan Li; Ning Wei; Jian Song; Jintao Liu; Jiajun Yuan; Rong Song; Li Liu; Lu Mei; Shuangshuang Yan; Yudong Wu; Rubing Pan; Weizhuo Yi; et al. (Environmental Research, 2023)

The association between greenery type and gut microbiome in schizophrenia: did all greenspaces play the equivalent role? - Ning Wei; Shusi Wang; Xuanxuan Li; Rubing Pan; Weizhuo Yi; Jian Song; Li Liu; Jintao Liu; Jiajun Yuan; Rong Song; Jian Cheng; Hong Su (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Characterization of airborne microplastics at different workplaces of the poly(ethylene:propylene:diene) (EPDM) rubber industry - Xiaoni Sun; Rong Song; Jintao Liu; Shuangshuang Yan; Yuxuan Li; Xiaoyu Jin; Yunfeng Liang; Yudong Wu; Lu Mei; Rubing Pan; Weizhuo Yi; Jian Song; et al. (Environmental Science and Pollution Research, 2023)

Dispersed Pd/alumina catalyst with finite iodine entry for boosted CO purification and dimethyl carbonate synthesis - Yun-Yun Zeng; Lu-Yang Qiao; Shan-Shan Zong; Rong Guo; Jian-Kai Cheng; Xin-Yi Cao; Zhang-Feng Zhou; Mao-Hong Fan; Yuan-Gen Yao (Chemical Engineering Journal, 2023)

Sulfurospirillum oryzae sp. nov., A Novel Nitrogen-Fixing Bacterium Isolated from Paddy Soil - Cheng-Jie Xie; Shang Yang; Rong Tang; Shuang Han; Guo-Hong Liu; Shun-Gui Zhou (Current Microbiology, 2023)

Sunshine duration and risks of schizophrenia hospitalizations in main urban area: Do built environments modify the association? - Li Liu; Qing Wu; Xuanxuan Li; Rong Song; Ning Wei; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Geothrix oryzisoli sp. nov., a ferric iron-reducing bacterium isolated from paddy soil - Shuang Han; Rong Tang; Shang Yang; Cheng-Jie Xie; Manik Prabhu Narsing Rao; Christopher Rensing; Guo-Hong Liu; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2023)

Molecular identification of a flavone synthase I/flavanone 3β-hydroxylase bifunctional enzyme from fern species Psilotum nudum - Jie Fu; Piao-Yi Wang; Rong Ni; Jiao-Zhen Zhang; Ting-Ting Zhu; Hui Tan; Jing Zhang; Hong-Xiang Lou; Ai-Xia Cheng (Plant Science, 2023)

Karst-ecological changes during the middle and late Holocene in Southwest China revealed by δ18O and δ13C records in a stalagmite - Rong Duan; Ting-Yong Li; Jun-Yun Li; Christoph Spötl; Hong-Chun Li; Hai-Bo Wang; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Jing-Li Zhou; Chao-Jun Chen; Tsai-Luen Yu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

A novel sulfate-reducing and nitrogen-fixing bacterium Fundidesulfovibrio soli sp. nov., isolated from paddy soils - Shang Yang; Rong Tang; Cheng-Jie Xie; Shuang Han; Christopher Rensing; Guo-Hong Liu; Shun-Gui Zhou (Archives of Microbiology, 2023)

Bacillus litorisediminis sp. nov., a Thermophilic Bacterium Isolated from Mangrove Sediment - Rong Tang; Shang Yang; Shuang Han; Cheng-Jie Xie; Guan-Min Huang; Manik Prabhu Narsing Rao; Guo-Hong Liu; Shun-Gui Zhou (Current Microbiology, 2023)

Fundidesulfovibrio agrisoli sp. nov., A Nitrogen-Fixing Bacterium Isolated from Rice Field - Shang Yang; Rong Tang; Shuang Han; Cheng-Jie Xie; Manik Prabhu Narsing Rao; Guo-Hong Liu; Shun-Gui Zhou (Current Microbiology, 2023)

A novel nitrogen-fixing bacterium, Propionivibrio soli sp. nov. isolated from paddy soil - Cheng-Jie Xie; Rong Tang; Shang Yang; Shuang Han; Christopher Rensing; Guo-Hong Liu; Shun-Gui Zhou (Archives of Microbiology, 2023)

Short-term exposure to air pollution is an emerging but neglected risk factor for schizophrenia: A systematic review and meta-analysis - Rong Song; Li Liu; Ning Wei; Xuanxuan Li; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Lu Mei; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Development and characterization of ultrastable emulsion gels based on synergistic interactions of xanthan and sodium stearoyl lactylate - Chunhuan Liu; Yunxing Li; Rong Liang; Hong Sun; Lei Wu; Cheng Yang; Yuanfa Liu (Food Chemistry, 2023)

Influence of different soil properties on the failure behavior of deposit slope under earthquake after rainfall - Bing Yang; Jiang-rong Hou; Zi-hong Zhou; Jin-cheng Gou (Journal of Mountain Science, 2023)

Correction to: Description of two nitrogen‑fixing bacteria, Geomonas fuzhouensis sp. nov. and Geomonas agri sp. nov., isolated from paddy soils - Shang Yang; Guo-Hong Liu; Rong Tang; Shuang Han; Cheng-Jie Xie; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2023)

Two ferric-reducing bacteria Geothrix terrae sp. nov. and Geothrix alkalitolerans sp. nov., isolated from paddy soil - Shuang Han; Rong Tang; Shang Yang; Cheng-Jie Xie; Manik Prabhu Narsing Rao; Guo-Hong Liu; Shun-Gui Zhou (Archives of Microbiology, 2022)

Description of two nitrogen-fixing bacteria, Geomonas fuzhouensis sp. nov. and Geomonas agri sp. nov., isolated from paddy soils - Shang Yang; Guo-Hong Liu; Rong Tang; Shuang Han; Cheng-Jie Xie; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2022)

The combined toxicity and mechanism of multi-walled carbon nanotubes and nano zinc oxide toward the cabbage - Mo Hong; Ji-Lai Gong; Wei-Cheng Cao; Rong Fang; Zhe Cai; Jun Ye; Zeng-Ping Chen; Wang-Wang Tang (Environmental Science and Pollution Research, 2022)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

Aquamicrobium zhengzhouense sp. nov., a Bacterium Isolated from Farmland Soil Applied with Amino Acid Fertilizer - Xiang Wang; Chun-Fu Zhou; Jia-Rong Cheng; Sheng-Fei Cao; Hong-Xing Yang; Jian-Rong Zhao (Current Microbiology, 2021)

Bi-allelic BRWD1 variants cause male infertility with asthenoteratozoospermia and likely primary ciliary dyskinesia - Ting Guo; Chao-Feng Tu; Dan-Hui Yang; Shui-Zi Ding; Cheng Lei; Rong-Chun Wang; Lv Liu; Xi Kang; Xiao-Qing Shen; Yi-Feng Yang; Zhi-Ping Tan; Yue-Qiu Tan; et al. (Human Genetics, 2021)

Late Cretaceous granitic magmatism and Sn mineralization in the giant Yinyan porphyry tin deposit, South China: constraints from zircon and cassiterite U–Pb and molybdenite Re–Os geochronology - Peng-Cheng Hu; Wei-Guang Zhu; Hong Zhong; Rong-Qing Zhang; Xiao-Yu Zhao; Wei Mao (Mineralium Deposita, 2021)

Phytochemical and antitumor studies on Cynanchum mongolicum (Maxim.) Kom - Yong-Cheng Yang; Yan-Ming Wang; Zi-Jian Rong; Li-Na Hong; Qian Zhang; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2020)

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

Two new benzophenones from endohydric moss Polytrichum Commune - Xu-Hong Duan; Jian-Cheng Zhao; Lin Li; Lin Pei; Pei He; Rong Wang (Natural Product Research, 2019)

Effect of Apolipoprotein E Genotypes on Huntington’s Disease Phenotypes in a Han Chinese Population - Xiao-Yan Li; Yan-Bin Zhang; Miao Xu; Hong-Rong Cheng; Yi Dong; Wang Ni; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2019)

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms - Jin-Cheng Xing; Jing Dong; Mao-Wen Wang; Chong Liu; Bao-Quan Zhao; Zhu-Gui Wen; Xiao-Mei Zhu; Hai-Rong Ding; Xiao-Hui Zhao; Li-Zhou Hong (Brazilian Journal of Botany, 2019)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Hepatic expression of transcription factors affecting developmental regulation of UGT1A1 in the Han Chinese population - Ya-li Nie; Hang He; Jiang-feng Li; Xiang-guang Meng; Liang Yan; Pei Wang; Shu-jie Wang; Hong-zheng Bi; Li-rong Zhang; Quan-cheng Kan (European Journal of Clinical Pharmacology, 2017)

Antioxidant and hyaluronidase inhibitory activities of diverse phenolics in Phyllanthus emblica - Min Xu; Hong-Tao Zhu; Rong-Rong Cheng; Dong Wang; Chong-Ren Yang; Takashi Tanaka; Isao Kouno; Ying-Jun Zhang (Natural Product Research, 2016)

Elliptic Shape Prior Dynamic Programming for Accurate Vessel Segmentation in MRI Sequences with Automated Optimal Parameter Selection - Da-Chuan Cheng; Sin-Kuo Chai; Shi-Rong Xu; Shing-Hong Liu (Journal of Medical and Biological Engineering, 2016)

Valproic Acid Influences MTNR1A Intracellular Trafficking and Signaling in a β-Arrestin 2-Dependent Manner - Ling-juan Hong; Quan Jiang; Sen Long; Huan Wang; Ling-di Zhang; Yun Tian; Cheng-kun Wang; Jing-jing Cao; Rong-rong Tao; Ji-yun Huang; Mei-hua Liao; Ying-mei Lu; et al. (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Ecotoxicity of two organophosphate pesticides chlorpyrifos and dichlorvos on non-targeting cyanobacteria Microcystis wesenbergii - Kai-Feng Sun; Xiang-Rong Xu; Shun-Shan Duan; You-Shao Wang; Hao Cheng; Zai-Wang Zhang; Guang-Jie Zhou; Yi-Guo Hong (Ecotoxicology, 2015)

Genetic diversity revealed by morphological traits and ISSR markers in 48 Okras (Abelmoschus escullentus L.) - Cong-Ying Yuan; Ping Wang; Pang-Pang Chen; Wen-Jun Xiao; Cheng Zhang; Shuai Hu; Ping Zhou; Hong-Ping Chang; Zhuang He; Rong Hu; Xiu-Tao Lu; Jia-Zhuo Ye; et al. (Physiology and Molecular Biology of Plants, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

The impact of the cognition of landscape experience on tourist environmental conservation behaviors - Yu-ling Zhang; Jie Zhang; Hong-Lei Zhang; Shao-wen Cheng; Yong-rui Guo; Jin-hai Ma; Jing-rong Sun (Journal of Mountain Science, 2015)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

A Proteomic Analysis of Placental Trophoblastic Cells in Preeclampsia–Eclampsia - Kaidong Ma; Hong Jin; Rong Hu; Yu Xiong; Shufeng Zhou; Peng Ting; Yan Cheng; Yan Yang; Pengyuan Yang; Xiaotian Li (Cell Biochemistry and Biophysics, 2014)

Early lethality of shRNA-transgenic pigs due to saturation of microRNA pathways - Zhen Dai; Rong Wu; Yi-cheng Zhao; Kan-kan Wang; Yong-ye Huang; Xin Yang; Zi-cong Xie; Chang-chun Tu; Hong-sheng Ouyang; Tie-dong Wang; Da-xin Pang (Journal of Zhejiang University-SCIENCE B, 2014)

The Report of Sustained Low-Efficiency Dialysis (SLED) Treatment in Fifteen Patients of Severe Snakebite - Junzhang Cheng; Dan Wang; Shouliang Hu; Hong Jiang; Hongzhu Lu; Qingfeng Lei; Juncheng Liu; Fanli Yuan; Rong Chen (Cell Biochemistry and Biophysics, 2014)

Effect of a single-dose rifampin on the pharmacokinetics of pitavastatin in healthy volunteers - Yao Chen; Wei Zhang; Wei-hua Huang; Zhi-rong Tan; Yi-cheng Wang; Xi Huang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2013)

What interests them in the pictures? — Differences in eyetracking between rhesus monkeys and humans - Ying-Zhou Hu; Hui-Hui Jiang; Ci-Rong Liu; Jian-Hong Wang; Cheng-Yang Yu; Synnöve Carlson; Shang-Chuan Yang; Veli-Matti Saarinen; Joshua D. Rizak; Xiao-Guang Tian; Hen Tan; Zhu-Yue Chen; et al. (Neuroscience Bulletin, 2013)

Microspore embryogenesis and production of haploid and doubled haploid plants in carrot (Daucus carota L.) - Jin-Rong Li; Fei-Yun Zhuang; Cheng-Gang Ou; Hong Hu; Zhi-Wei Zhao; Ji-Hua Mao (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Formaldehyde Impairs Learning and Memory Involving the Disturbance of Hydrogen Sulfide Generation in the Hippocampus of Rats - Xiao-Qing Tang; Yuan-Yuan Zhuang; Ping Zhang; Heng-Rong Fang; Cheng-Fang Zhou; Hong-Feng Gu; Hui Zhang; Chun-Yan Wang (Journal of Molecular Neuroscience, 2013)

Analysis of genetic diversity in the tuber mustard (Brassica juncea var. tumida Tsen et Lee) in the Yangtze river basin of China - Ping Fang; Fa-Bo Chen; Qi-Lun Yao; Ke-Cheng Yang; Guang-Fan Zhou; Yong-Hong Fan; Zhao-Rong Zhang; Jin-Juan Shen; Hong Zhang (Genetic Resources and Crop Evolution, 2013)

Synthesis of Benzimidazoles Containing Pyrazole Group and Quantum Chemistry Calculation of Their Spectroscopic Properties and Electronic Structure - Ren Tie-gang; Cheng Hong-bin; Zhang Jing-lai; Li Wei-jie; Guo Jia; Yang Li-rong (Journal of Fluorescence, 2012)

Preliminary proteomic analysis of circulating polymorphonuclear neutrophils from rabbits experiencing scald injury and Staphylococcus aureus sepsis - Pi-hong Zhang; Li-li Li; Ji-zhang Zeng; Liu-rong Yang; Li-cheng Ren; Peng-fei Liang; Xiao-Yuan Huang (Inflammation Research, 2010)

Phylogenetic analysis of Mycoplasma suis isolates based on 16S rRNA gene sequence in China - Rong-Qiong Zhou; Kui Nie; Han-Cheng Huang; Shi-jun Hu; Zuo-yong Zhou; Hong-Lin Luo (Veterinary Research Communications, 2009)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Allelopathic impact of artificially applied coumarin on Fusarium oxysporum f.sp. niveum - Hong-Sheng Wu; Waseem Raza; Dong-Yang Liu; Cheng-Long Wu; Ze-Shen Mao; Yang-Chun Xu; Qi-Rong Shen (World Journal of Microbiology and Biotechnology, 2008)

Polymorphisms in intron 1 of the porcinePOU1F1 gene - Cheng-Yi Song; Bo Gao; Shang-Hui Teng; Xiao-Yang Wang; Fei Xie; Guo-hong Chen; Zhi-Yue Wang; Rong-bin Jing; Jiu-De Mao (Journal of Applied Genetics, 2007)

Hydrogenation of ortho-nitrochlorobenzene on activated carbon supported platinum catalysts - Cheng-jun Jiang; Hong Yin; Zhi-rong Chen (Journal of Zhejiang University-SCIENCE B, 2005)